INTRODUCTION: MAPPING MIMETIC STUDIES - Lawtoo, Nidesh (Homo Mimeticus II, 2024)
With this epigrammatic affirmation reintegrating mimesis in the complex genealogy of Homo sapiens , the transdisciplinary thinker Edgar Morin (1921-) joined hands to bring the first volume of Homo Mimeticus to an end. This ending marked, in fact, a new beginning. Launching a new theory of imitation vital to facing the contemporary manifestations of mimesis that, under different masks, cast a long material shadow on the present and future, the goal of the first volume was to set new theoretical foundations for an emerging field we called mimetic studies, a transdisciplinary field now furthered in a planned trilogy on Homo